2020
DOI: 10.1111/ppc.12472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the cognitive stimulation therapy based on Roy's adaptation model on Alzheimer's patients’ cognitive functions, coping‐adaptation skills, and quality of life: A randomized controlled trial

Abstract: Purpose: This study aims to specify the effects of Cognitive Stimulation Therapy based on Roy's adaptation model (RAM) on Alzheimer's patients' coping and adaptation skills, cognitive functions, and quality of life (QOL).Design and methods: This is an experimental and randomized controlled trial.Patients in the experimental group received cognitive stimulation therapy (CST) based on RAM. Findings:The cognitive function level of the experimental group was found to be higher than that of the control group at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In addition, the mean MMSE scores of all selected studies ranged from 5.1 to 23.5. Meanwhile, among the 38 baseline data on demographic characteristics, three studies did not record baseline values of cognitive function in subjects ( Cheung et al, 2019 ; Nagy et al, 2021 ; Rai et al, 2021 ), and three studies did not report exact baseline age data ( Cavallo and Angilletta, 2019 ; Lok et al, 2020 ; Qi et al, 2021 ), but all conform to our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the mean MMSE scores of all selected studies ranged from 5.1 to 23.5. Meanwhile, among the 38 baseline data on demographic characteristics, three studies did not record baseline values of cognitive function in subjects ( Cheung et al, 2019 ; Nagy et al, 2021 ; Rai et al, 2021 ), and three studies did not report exact baseline age data ( Cavallo and Angilletta, 2019 ; Lok et al, 2020 ; Qi et al, 2021 ), but all conform to our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In meta‐analysis, studies identified as high‐risk in the quality appraisal were excluded. Studies (Burgener et al, 2008; i Ferrer & Del Valle, 2014; Lim et al, 2009; Lok et al, 2020; Tappne & Hain, 2013) that did not have a control group, mean score of outcomes at follow‐up or standard deviation values were also excluded from the meta‐analysis. Therefore, the meta‐analysis was performed on 15 studies (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, nurse‐led single nonpharmacological interventions were found to be effective in the meta‐analysis, and cognitive stimulation was the most common type of nurse‐led single nonpharmacological intervention, as it was implemented in 7 studies (Duru Aşiret & Kapucu, 2016; Hong & Kang, 2009; Lok et al, 2019; Lok et al, 2020; Tadaka & Kanagawa, 2007; van Bogaert et al, 2013; Wang, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that the improvements in these QoL dimensions were significantly higher in the experimental group. Previous studies targeting neuropsychiatric patients and healthy older adults have already reported the association between cognitive interventions and QoL improvement (e.g., Grasso et al [ 54 ]; Lok et al, [ 55 ]; Kazazi et al [ 56 ]), whereas others failed to find such an association (e.g., Orrell et al [ 57 ]). Potentially, since the QoL measures used included an assessment of cognition, the intervention modified our QoL results as well.…”
Section: Discussionmentioning
confidence: 99%